2018
DOI: 10.1080/15384101.2018.1502576
|View full text |Cite
|
Sign up to set email alerts
|

Senescence induction universally activates transposable element expression

Abstract: Senescent cells constitutively secrete inflammatory cytokines, known as the senescence-associated secretory phenotype (SASP). Previous work has implicated SASP in immune-mediated clearance of senescent cells; however, its regulation remains unknown. Our recent transcriptome profiling study has shown that human senescent human stem and progenitors (s-HSPCs) robustly express genomic transposable elements (TEs) and pathways of inflammation. Furthermore, hypomethylating agents have been previously shown to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
(76 reference statements)
3
31
0
Order By: Relevance
“…Preferential retrotransposition in yeast mother cells has been also found to be correlated with increased genome instability during replicative aging in S. cerevisiae (Patterson et al 2015). Age-related increase in the activity and mobility of transposable elements has been also reported in mammalian cells and tissues (De Cecco et al 2013a, b; Colombo et al 2018), however, no conclusive biological role(s) of these events have been provided. It has been observed that during normal aging several families of retrotransposable elements (RTEs) are transcribed in mouse tissues and in advanced age the expression culminates in active transposition (De Cecco et al 2013b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preferential retrotransposition in yeast mother cells has been also found to be correlated with increased genome instability during replicative aging in S. cerevisiae (Patterson et al 2015). Age-related increase in the activity and mobility of transposable elements has been also reported in mammalian cells and tissues (De Cecco et al 2013a, b; Colombo et al 2018), however, no conclusive biological role(s) of these events have been provided. It has been observed that during normal aging several families of retrotransposable elements (RTEs) are transcribed in mouse tissues and in advanced age the expression culminates in active transposition (De Cecco et al 2013b).…”
Section: Discussionmentioning
confidence: 96%
“…Altered expression of transposable elements can drive mutations in tumorigenesis and can be considered as a hallmark of cancer (Burns 2017). More recently, activation of transposable elements has been also documented in replicatively and stress-induced senescent human cells as well as during normal aging in mammalian somatic tissues (De Cecco et al 2013a, b; Colombo et al 2018; De Cecco et al 2019). However, little is known about the biological function(s) of age-associated increase in TE activity and related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…TEs can be transcribed from the genome [7] and have been demonstrated to play important roles in the mammalian embryogenesis [8,9], neurodevelopment [10,11], and immune functions [12,13]. Furthermore, aberrant expressions of TEs have been linked to cancers [14][15][16], neurodegenerative disorders [17,18], and immune-mediated inflammation [19,12]. Therefore, it has become increasingly important to explore biological roles of TEs expression.…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposons are made of Long Terminal Repeats (LTRs) and non-LTRs that include long interspersed nuclear elements (LINEs) and short interspersed nuclear elements (SINEs) that mobilize via a RNA intermediate, while DNA transposons mobilize and function through a DNA intermediate [ 4 6 ]. TEs can be transcribed from the genome [ 7 ] and have been demonstrated to play important roles in the mammalian embryogenesis [ 8 , 9 ], neurodevelopment [ 10 , 11 ], and immune functions [ 12 , 13 ]. Furthermore, aberrant expressions of TEs have been linked to cancers [ 14 16 ], neurodegenerative disorders [ 17 , 18 ], and immune-mediated inflammation [ 19 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposons are made of Long Terminal Repeats (LTRs) and non-LTRs that include long interspersed nuclear elements (LINEs) and short interspersed nuclear elements (SINEs) that mobilize via a RNA intermediate, while DNA transposons mobilize and function through a DNA intermediate[46]. TEs can be transcribed from the genome[7] and have been demonstrated to play important roles in the mammalian embryogenesis[8, 9], neurodevelopment[10, 11], and immune functions[12, 13]. Furthermore, aberrant expressions of TEs have been linked to cancers[1416], neurodegenerative disorders[17, 18], and immune-mediated inflammation[19, 20].…”
Section: Introductionmentioning
confidence: 99%